Prevalence and antibiotics resistance of Ureaplasma species and Mycoplasma hominis in Hangzhou, China, from 2013 to 2019 - Song, Jingjuan; Wu, Xuanlan; Kong, Yingying; Jin, Hong; Yang, Ting; Xie, Xinyou; Zhang, Jun (Frontiers in Microbiology, 2022)
Ureaplasma spp. and Mycoplasma hominis, frequent colonizers in the lower urogenital tract, have been implicated in various infections, with antibiotic resistance growing and varying regionally. This study aims to investigate the prevalence and antibiotic resistance profiles of Ureaplasma spp. and M. hominis in outpatients in Hangzhou, China, from 2013 to 2019. A total of 135,263 outpatients were examined to determine the prevalence of Ureaplasma spp. and M. hominis, including 48,638 males and 86,625 females. Furthermore, trends in antibiotic susceptibility of Ureaplasma spp. and M. hominis during 1999–2019 were analyzed. The cultivation, identification, and antibiotic susceptibility of the bacteria (ofloxacin, ciprofloxacin, erythromycin, clarithromycin, azithromycin, josamycin, tetracycline, doxycycline, and pristinamycin) were determined using the Mycoplasma IST2 kit. Our study indicated that the overall prevalence of total Ureaplasma spp./M. hominis was 38.1% from 2013 to 2019. Ureaplasma spp. were the most frequently isolated species (overall prevalence, 31.3%), followed by Ureaplasma spp./M. hominis coinfection (6.0%) and single M. hominis infection (0.8%). The prevalence of Ureaplasma spp. and M. hominis was significantly higher in females than in males, and the highest positive rates of total Ureaplasma spp./M. hominis were observed in both female and male outpatients aged 14–20 years. During 2013–2019, josamycin, tetracycline, doxycycline, and pristinamycin maintained exceptionally high activity (overall resistance rates, <5%) against both Ureaplasma spp. and M. hominis, but ofloxacin and ciprofloxacin showed limited activity (overall resistance rates, >70%). During 1999–2019, the rates of resistance to ofloxacin and ciprofloxacin increased against both Ureaplasma spp. and M. hominis but decreased to erythromycin, clarithromycin, azithromycin, tetracycline, and doxycycline against Ureaplasma spp. In conclusion, our study demonstrates a high prevalence of Ureaplasma spp. compared to M. hominis and Ureaplasma spp./M. hominis, and their distribution was associated with sex and age. Josamycin, doxycycline, and tetracycline are promising antibiotics that have remarkable activity against Ureaplasma species and M. hominis.